Intellectual Capital Disclosure by Listed Companies in Jordan: A Comparative Inter-sector Analysis - Krayyem Al-Hajaya; Mohammad Saleh Altarawneh; Bayan Altarawneh (International Review of Management and Marketing, 2019)
This study examines the level and quality of the disclosures of intellectual capital (IC) by listed companies in Jordan as a case for emerging economies, especially those from Arab nations. Using content analysis, 2016's annual reports of all 215 listed companies on the Amman Stock Exchange (ASE) were analyzed and compared for the main sectors: financial, service and manufacturing. The key findings indicate a low disclosure level of IC. The most disclosed components of IC were the items of internal capital. Financial companies were found to disclose the most items, followed by manufacturing firms and finally the service sector. This research has implications for policy makers and standard setters regarding mechanisms to boost the practice of IC disclosure in annual reports. This in turn enhances the quality of disclosed information as well as facilitating a better assessment of firm value. This research fills a void in the comparative study of IC disclosure practices among main sectors in the ASE, Jordan.